The role of aesthetic beauty of natural landscapes in supporting conservation efforts - Mariela Cervetto; Ofelia Gutiérrez; Walter Norbis; Daniel Panario (Discover Environment)
Abstract A landscape is the perceptible manifestation of a socio-ecosystem, where social and natural subsystems interact and co-evolve at different spatial and temporal scales. It is both a reality from a physical standpoint, and the representation we get of it. It is both tangible and intangible simultaneously, and relevant in the formation of territorial identities. In Uruguay, between two country models—the natural and the productive—natural landscapes are in a situation of extreme fragility. This research analyses the perceptions of the rural and urban population, with different levels of education, of Uruguay's natural landscapes. The concept of beauty, as a pleasant affective response, drives people into interacting with natural environments in search of well-being. For urban dwellers, this is expressed in their need to reconnect with nature. For the rural population, it creates territorial identities, attachments, feelings of belonging, and accompanies life trajectories. Therefore, it can be concluded that the aesthetic and spiritual values that society attributes to Uruguayan landscapes could play a crucial role in the formulation of effective public conservation policies.